Desenvolvimento de biomateriais micro e nanoestruturados baseados em compostos da família dos fosfatos de cálcio para aplicação em regeneração óssea e reconstituição dentária - Peixoto, Janaína Alves (2011)
The main aim of the present work is to study the effect of different maturation times (26 to 120h) and different heat treatments (100 to 600oC) in the morphology and particle or crystallite sizes of nanopowders of hydroxyapatite (HAP) produced by a controlled pre-cipitation method, where a solution containing Ca(NO3)2.4H2O is slowly mixed to a solution containing(NH4)2HPO4. The results of X-ray diffraction revealed the formation of hexagonal phase of HAP in all samples. The results of X-ray diffraction (XRD) re-vealed the formation of hexagonal phase of HAP in all samples. The Scherrer and Wil-liamson-Hall methods were used to obtain the crystallite sizes of the samples and the results revealed that the changes in the average nanoparticle sizes with the heat treat-ment temperature and maturation time is very small. The results of degree of crystallini-ty obtained by two different methods, FHWM peak (002) (Method 1) and the valley between the peaks (112) and (300) (Method 2), indicated that the higher crystallinity was obtained for the sample treated at 300oC. On the other hand the degree of crystallin-ity decreased as the maturation time increased and that was observed only by the meth-od 1. Raman spectroscopy results confirmed the formation of HAP observed in the XRD, since the spectra of all samples showed the typical vibrational modes of the(PO4)3-groups. The symmetric stretching modeν1, around 962cm-1, is very intense and that is characteristic of HAP crystalline matrix. TEM results showed the existence of well crystalline nanometric particles forming agglomerates. Such clusters are also observed on a larger scale in SEM images. Dynamic Light Scattering (DLS) measure-ments combined with those of TEM, X-rays and Raman confirm that the variations in the distribution of the particle sizes can be correlated to the degree of crystallinity of the samples as a function of the temperature of the heat treatment. And that can be ex-plained in terms of the evolution of the HAP formation in the initial stages during heat treatment. TEM images also confirms that is the morphology of the particles change as a function of the heat treatment temperature, but it does not happen with variations in the maturation time.